2021
DOI: 10.3389/fmed.2021.675573
|View full text |Cite
|
Sign up to set email alerts
|

Uremia-Associated Immunological Aging and Severity of COVID-19 Infection

Abstract: One year after the start of the COVID-19 pandemic it has become clear that some groups of individuals are at particular high risk of a complicated course of infection resulting in high morbidity and mortality. Two specific risk factors are most prominent, old age and the presence of co-morbidity. Recent studies have shown that patients with compromised renal function, especially those treated with renal replacement therapy or having received a kidney transplant are at a much higher risk for severe COVID infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 114 publications
2
12
0
1
Order By: Relevance
“…Thus, every increase in eGFR of 1 ml/min/1.73 m 2 increased the probability of developing IgGs by 3%. This observation is in line with a previous study 15 and might be explained by the fact that renal failure is associated with an impaired immune response especially with dysfunctional B cells 18,19 . In addition, other studies have indicated that calcineurin inhibitors, mTor inhibitors and age are additional factors influencing the immune response after SARS‐CoV‐2 vaccination in KTRs 4,15 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, every increase in eGFR of 1 ml/min/1.73 m 2 increased the probability of developing IgGs by 3%. This observation is in line with a previous study 15 and might be explained by the fact that renal failure is associated with an impaired immune response especially with dysfunctional B cells 18,19 . In addition, other studies have indicated that calcineurin inhibitors, mTor inhibitors and age are additional factors influencing the immune response after SARS‐CoV‐2 vaccination in KTRs 4,15 .…”
Section: Discussionsupporting
confidence: 89%
“…This observation is in line with a previous study 15 and might be explained by the fact that renal failure is associated with an impaired immune response especially with dysfunctional B cells. 18 , 19 In addition, other studies have indicated that calcineurin inhibitors, mTor inhibitors and age are additional factors influencing the immune response after SARS‐CoV‐2 vaccination in KTRs. 4 , 15 These associations could not be found in our study as the patient number taking these immunosuppression drugs was too low.…”
Section: Discussionmentioning
confidence: 99%
“…There is a dire need to explain the wide gamut of immune dysfunction in Covid-19 between mild and severe disease ( 35 ). Here, we incorporate a major correlation of Covid-1 severity; the proportion of CD8+ naïve T cells ( 12 , 23 , 36 ). As described by Moderbacher, et al, a higher proportion of these cells is protective in Covid-19.…”
Section: Discussionmentioning
confidence: 99%
“…Die COVID-19-Pandemie hat nachdrücklich verdeutlicht, wie vulnerabel die Gruppe der Patient:innen mit chronischen Nierenerkrankungen ist. Auch wenn es noch Jahre dauern wird, alle Aspekte der COVID-19-Erkrankung zu untersuchen und zu verstehen, die Einfluss auf den Verlauf von Nierenerkrankungen, die Dialyse und die Nierentransplantation haben, ist bereits jetzt klar, dass Patient:innen mit einer chronischen Nierenerkrankung nach einer SARS-CoV-2-Infektion eine schlechtere Prognose haben [ 70 , 71 ]. Und umgekehrt haben Patient:innen mit einem schweren Verlauf der COVID-19-Erkrankung ein erhöhtes Risiko, ein akutes Nierenversagen und im weiteren Verlauf eine chronische Niereninsuffizienz zu entwickeln [ 72 75 ].…”
Section: Covid-19-pandemie Und Niereninsuffizienzunclassified